Quasispecies characteristics in mother-to-child transmission of hepatitis B virus by next-generation sequencing. Issue 1 (July 2017) - Yang, Guifeng; Liu, Zhihua; Yang, Juncheng; Luo, Kangxian; Xu, Ying; He, Haitang; Fu, Qunfang; Yu, Shouyi; Wang, Zhanhui
Summary: Objectives: To identify within-host quasispecies characteristics of hepatitis B virus (HBV) in mothers and children infected via mother-to-child transmission (MTCT). Methods: Using next-generation sequencing (NGS), we analyzed sequences within the non-overlapping pre-core/core (pre-C/C) gene in 37 mother–child pairs. Results: Phylogenetic and Highlighter analyses suggested that both a single strain and multiple distinct strains may be transmitted in MTCT of HBV. However, analysis of reassembled viral sequences revealed a relatively narrow distribution of variants in children, which was confirmed by a lower viral diversity in children than that in mothers. New closely related variants with combinations of two to five high-frequency mutations were observed in seven children with elevated ALT levels; the new variants out-competed the transmitted maternal variants to become the dominant strains in five of them. Furthermore, 30 mutations with a frequency >1% of all viruses within-host were present in those children; the mutations caused 19 amino-acid substitutions. Interestingly, almost all were located within the well-known T-cell or B-cell epitopes. Conclusions: There are restrictive changes that occur in the early stages of chronic HBV infection through MTCT with different clinical consequences. These data might have important implications for future investigations of interrelated immunopathogenesis and therapeutic strategies. Highlights: Both a single HBV strain and multiple distinct strains may be transmitted in MTCT. A relatively narrow distribution of variants was observed in children. A lower viral diversity was observed in children than that in mothers. New dominant variants may occur during the early stages of chronic infection.